Identifikasi Masalah dan Upaya Pengembangan Kurikulum di SD Kristen Peristera - Mokhamad Nizar Maulana; Rodeo Novandi Pratama; Rifkha Rosana; Valliant Daffa Abdilla; Indana Zulfah; Amelia Noer Fitriana Effendy (Publikasi Inspirasi Indonesia, 2026)
This study aims to determine the problems in curriculum development at the elementary school level. Curriculum development at the elementary school level is an important aspect in the world of education. However, its implementation is often faced with obstacles such as inadequate facilities and infrastructure, limited educational resources, and lack of teacher training. The method used in this study uses a qualitative method. The data collection technique used is interviews. This study aims to identify obstacles at Paristera Christian Elementary School and provide solutions to improve the quality of learning. It is hoped that with a better understanding, schools can organize effective strategies in implementing the curriculum to meet the needs of students.